2002
DOI: 10.1128/jb.184.10.2587-2594.2002
|View full text |Cite
|
Sign up to set email alerts
|

Proteome and Transcriptome Analysis of the Virulence Genes Regulated by the VirR/VirS System in Clostridium perfringens

Abstract: The proteins under the control of the two-component system VirR/VirS in Clostridium perfringens were analyzed by using two-dimensional gel electrophoresis of the culture supernatant from the wild type and the virR mutant. Based on matrix-assisted laser desorption ionization-time of flight/mass spectrometry, seven positively regulated proteins and eight negatively regulated proteins were identified. Transcriptome analysis confirmed that 7 of the 15 proteins were regulated by the VirR/VirS system at the transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
3

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 35 publications
1
47
0
3
Order By: Relevance
“…The genome sequence of C. perfringens strain 13 was recently published, and VirR boxes were identified upstream of four additional open reading frames. Two of these open reading frames, CPE0845 and CPE0920, were found to encode hypothetical proteins, while CPE0846 and hyp7 encode the protease alpha-clostripain (40) and the regulatory RNA molecule, VR-RNA (6, 41), respectively. The expression of both CPE0846 and hyp7 has been demonstrated to be VirR dependent, and it is assumed that the expression of CPE0845 and CPE0920 is regulated by VirR in a similar manner (6,40,41).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The genome sequence of C. perfringens strain 13 was recently published, and VirR boxes were identified upstream of four additional open reading frames. Two of these open reading frames, CPE0845 and CPE0920, were found to encode hypothetical proteins, while CPE0846 and hyp7 encode the protease alpha-clostripain (40) and the regulatory RNA molecule, VR-RNA (6, 41), respectively. The expression of both CPE0846 and hyp7 has been demonstrated to be VirR dependent, and it is assumed that the expression of CPE0845 and CPE0920 is regulated by VirR in a similar manner (6,40,41).…”
Section: Resultsmentioning
confidence: 99%
“…By performing in vitro binding studies, we showed that VirR binds to each of these repeats independently, i.e., binding to the VirR boxes is not cooperative (11). The identification of the VirR boxes (11), in conjunction with the sequencing of the C. perfringens strain 13 genome (38), has led to the identification of putative VirRbinding sites upstream of other genes (38), two of which have been demonstrated to be regulated by VirR (40,41).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Sistema de dois componentes VirS/VirR, composto por uma proteína sensora de membrana e outra que funciona como regulador de transcrição (BANU et al, 2000;BA-THEIN et al, 1996;CHEUNG et al, 2009;SHIMIZU et al, 2002b); 2) Sistema de a uma camada celular de enterócitos Caco-2, provoca forte estímulo para a produção das toxinas α, β, β2, e perfringolisina. Aparentemente, este processo é mediado pelo Sistema VirS/VirR, mostrando-se a importância dos sistemas regulatórios na patogênese das doenças causadas por C. perfringens (McCLANE, 2010).…”
Section: Regulação Da Virulênciaunclassified